The literature of the Iglesia Ni Cristo an annotated bibliography, 1914-1980 - Plopino, Luz F. (1981)
The Iglesia ni Cristo (INC) is one of the many religious movements in the Philippines. The INC demonstrates unusual dynamism and power even in the secular affairs of Philippine society.